AN ANALYSIS ON FIGURATIVE LANGUAGE USED IN THOMAS HARDY'S POEMS - PALUPI , DWI (2007)
This research paper observes the figurative language on Thomas Hardy's poem. The aim of the study is to reveal the dominant figurative language used in Thomas Hardy's poems. Figurative language is one of the elements of poetry that has become the poet's way of expressing the art of his poems and communicating his language to know the poet's idea. It is expected that the result of this research will enrich the writer's knowledge of English literature, especially in understanding the meaning. The study uses a documentary data source, which is primary source. The primary sources are the text of poem itself: Ah Are You Digging On My Grave, the Man He Killed, Neutral Tones, I Look Into My Glass, I Need Not Go, The Convergence of The Twain, and Without Ceremony. The secondary sources are Thomas Hardy's biography and other data dealing with the research. The method of the data collection is observation and documentation. Based on the analysis, the writer concludes that Thomas Hardy uses some figures of speech in his poems. They are: 1). Hyperbole, 2). Metaphor, 3). Apostrophe, 4). Metonymy, 5). Paradox, 6). Personification, 7). Symbol, and 8). Understatement/Litotes. In addition, Thomas Hardy prefers to describe ideas, object and another by giving a pressure weight redundantly to get the intensive effect. Therefore, it can bring the readers imagination in his agreement with love, nature, reality, pessimistic, and the contrary states of the human soul. It is necessary to know and understand the meaning of poem through figures of speech used.